2013
DOI: 10.1016/j.beem.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone in the aging male

Abstract: Secretion of growth hormone (GH) and IGF-1 levels decline during advancing years-of-life. These changes (somatopause) are associated with loss of vitality, muscle mass, physical function, together with the occurrence of frailty, central adiposity, cardiovascular complications, and deterioration of mental function. For GH treatment to be considered for anti-aging, improved longevity, organ-specific function, or quality of life should be demonstrable. A limited number of controlled studies suggest that GH supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 51 publications
2
54
0
4
Order By: Relevance
“…The sale of purported antiaging products such as hormone replacement, including GH, has become a lucrative global industry, with the US market generating about USD 50 billion of revenue a year [21]. However, the use of such products has not been proven to be either effective or safe [22]. Specifically, alterations in GH/IGF-1 signaling with reductions in these somatotrophs appear to increase the life span in animal models [23].…”
Section: Discussionmentioning
confidence: 99%
“…The sale of purported antiaging products such as hormone replacement, including GH, has become a lucrative global industry, with the US market generating about USD 50 billion of revenue a year [21]. However, the use of such products has not been proven to be either effective or safe [22]. Specifically, alterations in GH/IGF-1 signaling with reductions in these somatotrophs appear to increase the life span in animal models [23].…”
Section: Discussionmentioning
confidence: 99%
“…This has major healthcare as well as socioeconomic implications, such as development of frailty, associated morbidity, increased hospitalisation and mortality (Goldspink, 2004;Mühlberg and Sieber, 2004;Volpi et al, 2004). The etiology of sarcopenia is not clearly understood, but (andropause), gradual decrease in dehydroepiandrosterone with age (adrenopause) and, impaired ability of the muscle cells to properly respond to circulating insulin may cause a decline in muscle protein synthesis and consequent loss of muscle mass and strength (Mühlberg and Sieber, 2004;Volpi et al, 2004;Giovannini et al, 2008;Sattler, 2013). Growth hormone elicits anabolic effects in the skeletal muscles through the hepatic production and release of IGF-1 (circulating or endocrine IGF-1) (Le Roith et al, 2001;Melmed et al, 2011), local production of mechanogrowth factor (MGF, IGF-1Ec) and IGF-1Ea (Giovannini et al, 2008;Sattler, 2013) and, reduced expression of myostatin, an inhibitor of muscle growth and promoter of adipogenesis (Marcell et al, 2001;Goldspink, 2004;Solomon and Bouloux, 2006;Perrini et al, 2010;Melmed et al, 2011;Puche and Castilla-Cortázar, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…For example, the secretion of GH from the pituitary is enhanced by acetylcholinesterase inhibitor (pyridostigmine) 7 and a primary mediator of growth hormone/insulin-like growth factor-1 (IGF-1) or GH-releasing hormone, which can stimulate secretion of acetylcholine from rat cortical slices and the hippocampus respectively 8,9 . It has recently been shown that age-related reductions in plasma GH, known as somatopause, is associated with increased incidence of cognitive impairment and AD, and can be compensated through GH treatment 10,11 . Various central effects of GH, such as cell genesis, neurogenesis 12 and angiogenesis 13 , suggest that GH administration may be effective in preventing the development or progression of AD 9,14,15 .…”
mentioning
confidence: 99%